A novel mutation in the glycogen synthase 2 gene in a child with glycogen storage disease type 0 - Pereira Maria; Luna Ana; Fortes Maria; Correa-Giannella Maria; Soggia Ana (BMC, 2010)
Abstract Background Glycogen storage disease type 0 is an autosomal recessive disease presenting in infancy or early childhood and characterized by ketotic hypoglycemia after prolonged fasting and postprandial hyperglycemia and hyperlactatemia. Sixteen different mutations have been identified to date in the gene which encodes hepatic glycogen synthase, resulting in reduction of glycogen storage in the liver. Case Presentation Biochemical evaluation as well as direct sequencing of exons and exon-intron boundary regions of the GYS2 gene were performed in a patient presenting fasting hypoglycemia and postprandial hyperglycemia and her parents. The patient was found to be compound heterozygous for one previously reported nonsense mutation (c.736 C>T; R243X) and a novel frameshift mutation (966_967delGA/insC) which introduces a stop codon 21 aminoacids downstream from the site of the mutation that presumably leads to loss of 51% of the COOH-terminal part of the protein. The glycemia and lactatemia of the parents after an oral glucose tolerance test were evaluated to investigate a possible impact of the carrier status on the metabolic profile. The mother, who presented a positive family history of type 2 diabetes, was classified as glucose intolerant and the father, who did not exhibit metabolic changes after the glucose overload, had an antecedent history of hypoglycemia after moderate alcohol ingestion. Conclusion The current results expand the spectrum of known mutations in GYS2 and suggest that haploinsufficiency could explain metabolic abnormalities in heterozygous carriers in presence of predisposing conditions.